2017
DOI: 10.1016/j.jallcom.2016.08.254
|View full text |Cite
|
Sign up to set email alerts
|

Improving mechanical and magnetocaloric responses of amorphous melt-extracted Gd-based microwires via nanocrystallization

Abstract: We report on the structural, mechanical, and magnetocaloric properties of annealed meltextracted Gd 53 Al 24 Co 20 Zr 3 amorphous microwires of ~70 m diameter. During heat treatment small islands of nanocrystallities are generated and isolated in the amorphous region for the wires. The size of the nanocrystallities ranges from 5 nm to 10 nm. The observed lattice distortion from the nanocrystallities causes changes in the magnetic properties of the wires. The annealing temperature of 100 ℃ has the largest stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This observation is not found for 5 T. Furthermore, it is observed that the ΔS M peaks of the microwires are maintained when annealed to 75 × 10 6 A m −2 but for 100 × 10 6 A m −2 of annealing, it shows a 22% reduction, compared with that of the as-cast state. This can be ascribed to the decreased magnetic moment of amorphous phase, arising from the reduction of Co content [35,53], which is observed from the EDS results (Table S2 and Fig. S3).…”
Section: Magnetocaloric Propertiesmentioning
confidence: 75%
See 2 more Smart Citations
“…This observation is not found for 5 T. Furthermore, it is observed that the ΔS M peaks of the microwires are maintained when annealed to 75 × 10 6 A m −2 but for 100 × 10 6 A m −2 of annealing, it shows a 22% reduction, compared with that of the as-cast state. This can be ascribed to the decreased magnetic moment of amorphous phase, arising from the reduction of Co content [35,53], which is observed from the EDS results (Table S2 and Fig. S3).…”
Section: Magnetocaloric Propertiesmentioning
confidence: 75%
“…Furthermore, the appearance of some nanocrystals leads to minor compositional difference between the amorphous matrix and nanocrystalline phase, leading to the widening of the T C distribution and improving the relative cooling power (RCP) by 7%. MCE enhancement is found for conventional alloys exhibiting amorphous/nanocrystalline dual-phase structures [6, [30][31][32][33][34][35], whereby those Gd-based compositions show an improve-ment of up to ~84% and ~21% in the values of maximum magnetic entropy change ( S M max ) and refrigeration capacity (RC) (for 5 T), respectively. In particular, a very recent report by Feng et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure Gd, as the benchmark magnetic refrigerant, is commonly used in the active magnetic regenerator prototypes . In particular, Gd metal could be produced into different shapes due to its good mechanical properties, such as thin plate, sphere, and microwire, and it has been demonstrated that microwire is more desirable for realizing a higher cooling performance . However, Gd metal also has its disadvantages such as relatively low magnetic entropy change (Δ S M ), limited availability, and expensive price that hinder its large‐scale commercialization.…”
Section: Curie Temperature (Tc) Magnetic Entropy Change (δSm) Adiabmentioning
confidence: 99%
“…Very recently, some heavy rare-earth (HRE)-based intermetallic compounds are found to exhibit large/giant MCE [8][9][10][11][12], however, only limit to around their own T C . It also has been theoretically shown that rod-or wire-shaped magnetic refrigerant materials are more suitable for actual cooling devices than their spherical counterparts [30,31], thus, the MCE in these type magnetic materials have been experimentally investigated recently, and some of them could outstanding candidate for active MR [26,[32][33][34]. Moreover, to our knowledge, no systematically research related to the triple HRE-based amorphous alloys has been reported.…”
mentioning
confidence: 99%